Venous thromboembolism and severe COVID-19: a Mendelian randomization trial and transcriptomic analysis - Chen, Liang; Dai, Xiaoting (Frontiers in Immunology, 2024)
Introduction Venous thromboembolism (VTE) is known to be intricately linked to severe COVID-19 (sCOVID-19) occurrence. Herein, we employed univariable Mendelian randomization (MR) and transcriptome analysis to predict the causal association and associated signaling networks between VTE and sCOVID-19. Methods Potential VTE and sCOVID-19 association was assessed using MR-Egger, weighted median, simple mode, weighted mode, and inverse variance weighted (IVW) regression. We conducted independent univariable analyses involving VTE and sCOVID-19. Using heterogeneity, pleiotropy, and the Leave-One-Out examinations, we performed sensitivity analyses. Thereafter, we performed transcriptome analysis of the GSE164805 dataset to identify differentially expressed genes (DEGs) linked to single nucleotide polymorphisms (SNPs). Lastly, we conducted immune analyses. Results Based on our univariable analysis, VTE was a strong indicator of sCOVID-19 development, and it was intricately linked to sCOVID-19. We further conducted sensitivity analysis to demonstrate the reliability of our results. Using differential analysis, we identified 15 major genes, namely, ACSS2, CEP250, CYP4V2, DDB2, EIF6, GBGT1, GSS, MADD, MAPK8IP1, MMP24, YBPC3, NT5DC3, PROCR, SURF6, and YIPF2, which were strongly connected to suppressive adaptive immune as well as augmented inflammatory cells. In addition, we uncovered strong associations with most differential immunologic gene sets, such as, the Major Histocompatibility Complex (MHC), immunoactivators, and immunosuppressors. Conclusion Herein, we demonstrated we strong association between VTE and enhanced sCOVID-19 risk. We also identified 15 DEGs which potentially contribute to the shared immunologic pathogenesis between VTE and sCOVID-19.